2009
DOI: 10.1094/pdis-93-7-0741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mefenoxam, Phosphonate, and Paclobutrazol on In Vitro Characteristics ofPhytophthora cactorumandP. citricolaand on Canker Size of European Beech

Abstract: Phytophthora citricola and P. cactorum cause bleeding cankers that lead to the death of mature European beech (Fagus sylvatica) in the northeastern United States. The effects of two fungicides and a plant growth regulator on in vitro pathogen characteristics and on canker expansion were investigated. In the first experiment, 16 single-spore isolates (11 P. citricola and 5 P. cactorum) were grown on clarified V8 juice agar amended with (i) 0 to 20 μg a.i./ml of mefenoxam, (ii) 0 to 301,429 μg a.i./ml phosphonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…Phytophthora pini was the most frequently isolated species from cankers and rhizosphere soil of infected beech whereas P. cactorum and P. cambivora were found less frequently in cankers or soils under affected trees. However, although isolates of the aforementioned species reportedly cause considerable damage to root systems of young beech under controlled conditions (Fleischmann 2002, Weiland et al 2009, 2010, we found no signifi cant difference in the frequency of isolation for P. pini, or all three species collectively, from rhizosphere soil between infected and asymptomatic European beech at GWC as well as PFA. The absence of a distinct association between Phytophthora spp.…”
Section: Year (Annual Ring)contrasting
confidence: 61%
See 1 more Smart Citation
“…Phytophthora pini was the most frequently isolated species from cankers and rhizosphere soil of infected beech whereas P. cactorum and P. cambivora were found less frequently in cankers or soils under affected trees. However, although isolates of the aforementioned species reportedly cause considerable damage to root systems of young beech under controlled conditions (Fleischmann 2002, Weiland et al 2009, 2010, we found no signifi cant difference in the frequency of isolation for P. pini, or all three species collectively, from rhizosphere soil between infected and asymptomatic European beech at GWC as well as PFA. The absence of a distinct association between Phytophthora spp.…”
Section: Year (Annual Ring)contrasting
confidence: 61%
“…Similarly, P. cactorum and P. cambivora are also widely distributed throughout temperate regions of N. America, and both are pathogenic on numerous plant species (Erwin andRibeiro 1996, Farr andRossman 2013). The extensive host-ranges and ubiquitous distributions of these pathogens in forest and urban landscapes suggest that their involvement in bleeding canker of European beech will continue, necessitating the long-term monitoring as well as chemical and cultural management of high-valued trees (Weiland et al 2009). The effectiveness of phosphite fungicide(s) on eradicating Phytophthora spp.…”
Section: Dmentioning
confidence: 99%
“…Amendment of potting media with 5% biochar did not prevent lesion development or increase biomass as well as treatment with salts of phosphorous acid, a material known to induce resistance against Phytophthora spp. (Daniel and Guest, 2006;Daniel et al, 2005;Garbelotto et al, 2009;Jackson et al, 2000;Weiland et al, 2009). However, based on this study and previous studies involving other pathogen/host combinations Harel et al, 2012), it appears that amendment of rooting media with 5% biochar has the potential to induce some level of resistance against a wide range of pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical and non-chemical management options are increasingly being sought to preserve valuable infected specimen trees and protect non-infected hosts. Chemical products containing phosphorous acids or derivatives have often been found most effective and are widely recommended for use against Phytophthora bleeding cankers (Garbelotto et al, 2009;Weiland et al, 2009). Systemic induced resistance (SIR) is the mechanism underlying Phytophthora disease reduction or prevention after treatment with phosphorous acids (Daniel and Guest, 2006;Daniel et al, 2005;Jackson et al, 2000).…”
mentioning
confidence: 99%
“…In other variant, fosetyl-Al reduced canker expansion by 86 -88 %, while mefenoxam reduced canker development by 52 -80 % (Browne & Viveros, 2005). Curative bark drench applications of phosphonate on beech saplings inoculated with Phytophthora citricola significantly limited canker expansion on infected trees (Weiland et al, 2009). Several experiments have been done on chemical control of oak wilt, caused by Ceratocystis fagacearum, and Dutch elm disease, caused by Ophiostoma ulmi.…”
Section: Curative Effects Of Fungicides In Management Of Vascular Wilmentioning
confidence: 99%